Entrepreneurial Competence and Business Sustainability of Rural Agripreneurs in West Sumatra - Putra, Erwin Syah; Amalia, Rizki; Pane, Yonson (Maroon Journal De Management, 2025)
Agriculture remains the backbone of rural livelihoods in West Sumatra, where farming continues to provide both income and food security for local communities. However, the sustainability of agribusiness ventures extends beyond land ownership and resource availability; it critically depends on the entrepreneurial competence of agripreneurs to anticipate risks, plan strategically, and innovate within increasingly competitive markets. This study examines the influence of entrepreneurial competence on business sustainability among rural agripreneurs in West Sumatra using a quantitative survey design involving 120 randomly selected respondents. Data were collected through structured questionnaires encompassing demographic characteristics, entrepreneurial competence dimensions business planning, marketing, and financial management and sustainability indicators across economic, social, and environmental domains. Statistical analysis revealed that agripreneurs possessed moderate competence in business planning and marketing but exhibited deficiencies in financial literacy and environmental stewardship. Business planning and financial management were identified as the strongest predictors of sustainability, while marketing competence showed a weaker but positive association. Despite contributing to local economic growth, limited strategic foresight and low adoption of sustainable and digital practices constrained long-term viability. Strengthening entrepreneurial competence through targeted training and policy interventions is therefore essential to enhance resilience, competitiveness, and sustainability among rural agripreneurs in West Sumatra.